2021
DOI: 10.3389/fsufs.2021.664531
|View full text |Cite
|
Sign up to set email alerts
|

Biofumigation With Pellets of Defatted Seed Meal of Brassica carinata: Factors Affecting Performance Against Phytophthora nicotianae in Pepper Crops

Abstract: Phytophthora nicotianae is the pathogen that causes root and crown rot disease in open field paprika pepper crops of Extremadura (central-western Spain). A field experiment was established during spring, a period compatible with the pepper crop cycle in this region, to evaluate the effects of biofumigation with pellets of Brassica carinata defatted seed meal, at the rate recommended by the manufacturer (3 tons ha−1), on the survival and infectivity of P. nicotianae chlamydospores inoculum. Furthermore, three b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…The resulted values were 1.41, 1.51, 1.75 and 4.28% for control soil, D, 10D and 100D soils, respectively; being the soil under investigation a clay loam soil, where OM% results in a low content in the range of 1.2-2.2% and in high content in the range >3.0%, it can be concluded that only the addition of seed meal at 100D really improves the OM content of the soil under experiment, supplying a very high amount of fresh organic matter. In contrast, the addition of the meal at doses D and 10D let stand the soil in the same class of OM content as the control soil, even if a slight increase is recorded, similarly to what was observed by Serrano-Pérez et al [57] at the dose of 3 ton/ha.…”
Section: Soil Organic Carbonsupporting
confidence: 81%
See 3 more Smart Citations
“…The resulted values were 1.41, 1.51, 1.75 and 4.28% for control soil, D, 10D and 100D soils, respectively; being the soil under investigation a clay loam soil, where OM% results in a low content in the range of 1.2-2.2% and in high content in the range >3.0%, it can be concluded that only the addition of seed meal at 100D really improves the OM content of the soil under experiment, supplying a very high amount of fresh organic matter. In contrast, the addition of the meal at doses D and 10D let stand the soil in the same class of OM content as the control soil, even if a slight increase is recorded, similarly to what was observed by Serrano-Pérez et al [57] at the dose of 3 ton/ha.…”
Section: Soil Organic Carbonsupporting
confidence: 81%
“…Other studies conducted with B. carinata pellets at similar doses to 10D β-glucosidase and phosphatase activities were not significantly different from the control [57,85]. On the contrary, for Zaccardelli et al [22], the β-glucosidase and phosphatase are significantly increased compared to control after one month, and the arylsulphatase seems to be influenced in the short term with a slight increase compared to the control followed by a stabilisation as observed in the present study at the same dose tested (10D).…”
Section: Soil Enzymatic Activitiesmentioning
confidence: 63%
See 2 more Smart Citations
“…In the IF block, Brassica carinata pellets were used repeatedly, while in the PD block, it was tomato plant debris. Núñez-Zofio et al [34] and Serrano-Pérez et al [59] reported that Brassica carinata pellets (with biosolarization) showed a limited capacity to improve the chemical quality of the soil. The organic amendment could not improve any of the chemical properties of the soil versus a treatment without the addition of any organic amendment and without applying solarization.…”
Section: Evaluation Of Seedling Growth In a Controlled Environment Ch...mentioning
confidence: 99%